School administration and supervision - Gregorio, Herman C. (Quezon City, Philippines : Garotech Publishing, 1961)
The many changes in educational thought and practice in the past few years had considerable effect on school administration and supervision. The increasing size of the educational enterprise and the broadening concepts of the role of leadership are a few of the forces which are evolving. a newer definition of the administrative and' supervisory functions, and a re-evaluation of the role of the administrator and supervisor in the Philippine school system. In this country, there is a rapidly growing recognition that democratic administration and supervision are necessary to the development and operation of a democratic education.
Chapter I. The Meaning and scope of school administration and supervision -- Chapter II. Functions of school administration and supervision -- Chapter III. Fundamental principles of administration and supervision -- Chapter IV. Legal bases of school administration and supervision -- Chapter V. Administrative and supervision organization of the department of education and culture -- Chapter VI. Administrative and supervisory organization of the bureau of elementary education -- Chapter VII. The administrative and supervisory organization of the bureau of secondary education -- Chapter VIII. Administrative and supervisory organization of the bureau of higher education -- Chapter IX. The administrative and supervisory organization of the regional office -- Chapter X. Classroom visit and observing the teaching-learning situation -- Chapter XI. Administrative and supervisory uses of test and measurement -- Chapter XII. Organization of the course of instruction as an administrative and supervisory function -- Chapter XIII. Administration and supervision of extra-class activities -- Chapter XIV. The Administration of pupil guidance and discipline -- Chapter XV. Administrative control of school plant, ground, and equipment -- Chapter XVI. Administration of teaching personnel -- Chapter XVII. In-service education of teachers as an administrative -- Chapter XVIII. Integrating the school and community as an administrative and supervisory function -- Chapter XIX. Financing education as an administrative function -- Chapter XX. Evaluating the results of school administration and supervision -- Chapter XXI. Code of professional ethics and academic freedom.
Includes index.
Keywords: SCHOOL MANAGEMENT AND ORGANIZATION